Perancangan UI/UX Aplikasi Stunting Your Buddy dengan Metode User-Centered Design - Putra, Anak Agung Adi Wiryya; Wirdianthi, Ni Luh Risma Putri; Azzaky, Renald Kevin (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2025)
The aim of this study is to design a mobile application that can assist in handling stunting in Panjer Village, Bali. Stunting is a condition where a child cannot grow to their optimal height according to the height of a child of their age. In this digital era, education can be conducted through various platforms, such as applications that are now commonly used. Based on a field survey that has been conducted by researching the needs of users one and two, Your Buddy will be designed to help provide education for young women about stunting prevention. Furthermore, this application will serve as an intermediary for pediatric specialists to provide education regarding stunting. This research focuses on an application that will function for stunting prevention education, requiring improvements in terms of appearance (UI) and usability (UX) to make it more appealing and user-friendly. To achieve this goal, this study will utilize the User Centered Design (UCD) method. The UCD method consists of four stages: specify the context of use, specify user and organizational requirements, produce design solutions, and evaluate design against user requirements. After testing several potential users, a final SUS score of 87.5 was obtained, which falls into point B with an Excellent category. The design of the Your Buddy application is proven to have quality that meets user expectations, but in the future, it is recommended to add AI features and increase the number of respondents to expand this research.